Surgery is Still Required to Treat Bronchiectasis - SAIMA SULTAN, FARMAN ALI, GHULAM SHABBIR PERVEZ (Journal of Fatima Jinnah Medical University, 2018)
Role of surgery has been reduced to a great deal in developed countries owing to vaccination and antibiotics but it still presents as a threat in developing countries. We analyzed our patients who were submitted for surgery with a diagnosis of Bronchiectasis. Material and Methods: During the year 2007- 2008 (Jan - Dec) we received 45 patients diagnosed as having Bronchiectasis.The age ranged from 7-40 years with maximum patients in age group 1-20 years(35).The chief presenting complaints were Excessive productive cough for more than 2 years = 42, Recurrent chest infections = 39 and haemoptysis = 30.2 patients had Kartegener`s syndrome.30 patients had no other reason to have acquired disease while 5 had a history of being treated as tuberculosis and 10 with a history of foreign body inhalation. The diagnosis was made on the basis of clinical symptoms and CT scan. 29 patients were operated while others were not found fit for surgery (Bilateral disease = 13; other reasons 3). Results: The surgical procedure done in these cases were Lobectomy (1 lobe) = 20; More than one lobe resection = 7 Wedge resection = 2 . All were followed up for at least 1 year. The postop complications encountered were increased post op bleeding = 3 and bronchopleural fistula =2. However these complications settled in a week’s time. 25 patients had complete regression of symptoms while3 had an improvement in symtomtology while 1 had no improvement. Conclusion: Surgery can be of great help in selective cases of Bronchiectasis where the medical treatment fails or cannot be continued for a proper duration. It comes across with a minimal complications and a satisfactory achievement